Business Strategy, Multinational Companies, Integrated Reporting, and Tax Avoidance - Putri Nurmala; Trisna Dwi Febianti; Akhmad Sigit Adiwibowo (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2024)
This research investigates the relationship between corporate strategy, multinational corporations, and integrated reporting on tax avoidance. A quantitative investigation depends on secondary data sources to collect its findings. This study's population consists of companies registered to trade on the Indonesia Stock Exchange between 2017 and 2021. The research was conducted in Indonesia. The research sample was obtained using an intended sampling approach, and as a result, the total number of companies in the sample was 90. This study found that multinational firms and integrated reporting had little impact on tax avoidance. It was revealed, however, that corporate strategy has a significant negative impact on tax avoidance. It is now uncommon to examine the impact of integrated reporting on tax avoidance, which is one of the reasons this study is so intriguing.